POLITICAL RELATIONS THROUGH PRISM OF SOCIOLOGY - Вікторія Леонідівна Погрібна; Ігор Валерійович Штана (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2018)
Problem setting. Today political sociology requires not only critical but also structural analysis of politics, creation of corresponding theoretical and methodological tool, one of major constituents of that there are research and prognostication of political relations and processes.